Preterm birth and its associated factors among women of reproductive age in Zambia: a survey analysis - Mutale Sampa; Atupele Chisiza; Mwiche Musukuma; Ronald Fisa; Leah Kamulaza; Wilbroad Mutale (BMC Pregnancy and Childbirth)
Abstract Background Preterm birth is the leading cause of death among children under five globally, with the highest burden in low- and middle-income countries (LMICs), particularly in Sub-Saharan Africa (SSA). Prevalence varies widely, ranging from 5% in high-income countries to 18% in LMICs. Despite its public health significance, Zambia lacks comprehensive nationally representative data on preterm birth. This study aimed to determine the prevalence and associated factors of preterm birth using data from the Zambia Demographic and Health Survey (ZDHS). Methods The study analyzed data from the 2018 ZDHS, which used a two-stage stratified cluster sampling design. A total of 10,962 women aged 15–49 years who had a live birth within five years of the survey were included. Survey analysis techniques were used to account for the DHS complex sampling design. Stepwise survey logistic and log-linear regressions were fitted to identify factors associated with preterm birth. A p-value of < 0.05 was considered statistically significant. Results The prevalence of preterm birth was 7%. Women with a parity of 10 or more had significantly increased prevalence of preterm birth (prevalence ratio (PR) = 2.15, 95% CI: 1.14–4.06, p = 0.018) compared to those with fewer than five births. Women who attended four or more antenatal care (ANC) visits had reduced prevalence of preterm birth (PR = 0.54, 95% CI: 0.46–0.65, p < 0.001). A history of abortion was also associated with higher odds of preterm birth (PR = 1.48, 95% CI: 1.14–1.93, p = 0.004). Conclusion Preterm birth remains a critical public health concern in Zambia, with a prevalence of 7%, aligning closely with regional SSA estimates (~ 12% per WHO). Key risk factors include high parity, a history of abortion, and cesarean delivery, while older maternal age and frequent ANC visits are protective. These findings underscore the need to strengthen ANC services and implement targeted interventions for high-risk women to reduce the burden of preterm birth in Zambia.